Prevalence and distribution of antimicrobial resistance profile of Escherichia coli isolated from various local fish markets in Dhaka city, Bangladesh (Journal of Bangladesh Academy of Sciences, 2022)
Considering the importance of the fish and fish products as a vital part of the human diet in Bangladesh, the study aimed to estimate the microbial load, identify the E. coli and observe the isolates antibiogram pattern. Standard plate count technique, as well as the 3-tube most probable number (MPN) method, were applied to estimate the total viable bacteria (TVB) and total coliforms (TC), total fecal coliforms (TFC), and E. coli, respectively. Approximately 61.91% of samples fell into the marginally acceptable limit for TVB count, while 66.67% and 95.25% of examined species exceeded the threshold limit for TC and TFC, respectively (p